2011
DOI: 10.1111/j.1476-4431.2010.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood gas analysis and cooximetry in retired racing Greyhounds

Abstract: Objective The purposes of this study were to evaluate the oxygen affinity of hemoglobin (Hb) in healthy retired racing Greyhounds via cooximetry, and to establish reference intervals for blood gases and cooximetry in this breed. Design Prospective clinical study. Setting University Teaching Hospital. Animals Fifty-seven Greyhounds and 30 non-Greyhound dogs. Interventions Venous blood samples were collected from the jugular vein and placed into heparinized tubes. The samples were analyzed within 30 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…High HGB concentration and PCV in Greyhounds was suggested to be a compensatory change secondary to decreased oxygen delivery to the tissues (low P 50 ), as is seen in people with high‐affinity hemoglobinopathies . We recently conducted additional studies on high‐affinity HGB and its function in RRGs, using blood gas analysis with cooximetry and confirmed low P 50 and higher oxygen content and oxygen‐binding capacity of HGB in Greyhounds . In a different study, we found that HGB in Greyhounds has a few unique amino acid mutations that are relevant to the oxygen affinity properties, and alter the position of the globin chains .…”
Section: Literature Reviewmentioning
confidence: 80%
See 1 more Smart Citation
“…High HGB concentration and PCV in Greyhounds was suggested to be a compensatory change secondary to decreased oxygen delivery to the tissues (low P 50 ), as is seen in people with high‐affinity hemoglobinopathies . We recently conducted additional studies on high‐affinity HGB and its function in RRGs, using blood gas analysis with cooximetry and confirmed low P 50 and higher oxygen content and oxygen‐binding capacity of HGB in Greyhounds . In a different study, we found that HGB in Greyhounds has a few unique amino acid mutations that are relevant to the oxygen affinity properties, and alter the position of the globin chains .…”
Section: Literature Reviewmentioning
confidence: 80%
“…Tracings were obtained after 120–180 minutes of running time at 37°C (Table ). References intervals for blood gases are reported from our previous study (Table ) …”
Section: Literature Reviewmentioning
confidence: 99%
“…These differences include lower WBC, neutrophil (NEU), and platelet (PLT) counts; higher HCT, HGB concentration, and RBC counts; and an atypical eosinophil (EOS) morphology . Retired racing Greyhounds also have high‐affinity HGB . On the other hand, there are significant increases in HCT, total plasma protein (TP) and HGB, as well as RBC, WBC, NEU, and lymphocyte (LYM) counts after exercise .…”
Section: Introductionmentioning
confidence: 99%
“…For the present study, the coefficient of variation of measurement for P O 2 was 1.6% and 2.2% for CO 2 . For each sample, O 2 saturation was calculated based on P O 2 , P CO 2 , pH and rectal temperature (Kelman, 1966(Kelman, , 1967(Kelman, , 1968 and an assumed partial pressure of O 2 at 50% saturation of haemoglobin of 30 mmHg, as has been reported previously for canine blood (Cambier et al 2004;Zaldivar-Lopez et al 2011).…”
Section: Blood Gas Measurementsmentioning
confidence: 99%
“…The arterial blood gas analyser (ABL80 FLEX; Radiometer), being configured for the human haemoglobin spectrum, did not allow for co-oximetry of canine blood for direct O 2 saturation measurement. As such, O 2 saturation was calculated based on P O 2 , P CO 2 , pH, temperature (Kelman, 1966(Kelman, , 1967(Kelman, , 1968 and an assumed P 50 (partial pressure of oxygen at 50% saturation) of haemoglobin of 30 mmHg (Cambier et al 2004;Zaldivar-Lopez et al 2011). It is doubtful that the difference in proximal vs. distal pulmonary artery O 2 saturation can be explained by inaccuracies of its determination because the same P 50 was used for estimating saturation from all blood samples and thus they should all be affected similarly by any uncertainty.…”
Section: Limitationsmentioning
confidence: 99%